MEMAKSIMALKAN MANFAAT MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PEMASARAN YANG EFEKTIF - Agus Hindarto Wibowo; Widuri Asih, Endang; Sulistyaningsih, Eka; Mawadati, Argaditia; Ustyannie, Windyaning (DHARMA BAKTI, 2023)
According to Kementerian Koperasi dan UKM Kementerian Koperasi UMKM, there is a significant increase in UMKM in Indonesia, this makes UKM must be able to compete in business, one of which uses social media Instagram. Instagram users have a very large amount globally, so it is very good to be used for the promotional media of UKM that are owned. Counseling and practice of optimizing Instagram accounts is very important to do, so that products from UKM can be known by the wider community. At present the business actors of OK OCE ADMA members have not maximized the use of Instagram social media well. The results of counseling and practices of account optimization implemented, business people at OK OCE ADMA are satisfied and hope in the future can be carried out further assistance.